FDA-Approved Small Molecules in 2022: Clinical Uses and Their Synthesis - Davide Benedetto Tiz; Luana Bagnoli; Ornelio Rosati; Francesca Marini; Claudio Santi; Luca Sancineto (MDPI AG, 2022)
This review describes the recently FDA-approved drugs (in the year 2022). Many of these products contain active moieties that FDA had not previously approved, either as a single ingredient or as part of a combination. These products frequently provide important new therapies for patients with multiple unmet diseases. The diverse small molecules are described according to the date of approval and their syntheses is discussed. This review comprises classical chemical scaffolds together with innovative drugs such as a deuterium-containing drug.